1999
DOI: 10.1037/1089-2680.3.1.44
|View full text |Cite
|
Sign up to set email alerts
|

Potential Sex Differences Remain Understudied: A Case Study of the Inclusion of Women in HIV/AIDS-Related Neuropsychological Research

Abstract: As an illustration of women's representation in clinical research, a comprehensive literature review of HIV/AIDS-related neuropsychological research was conducted. The goals of this study were to document whether women have been included in (a) HIV-related neurological and neuropsychological research studies; (b) percentages comparable to their representation in the population of persons with HIV/AIDS; (c) studies using numbers sufficient to allow data analyses by sex (N ≥ 30); and (d) data analyses conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 52 publications
0
19
0
Order By: Relevance
“…Close identification of the virus with gay men, and later injection drug users, meant that researchers failed to recognize or focus on heterosexual transmission for many years after the first cases were diagnosed in the US. Even by the 1990s, when it was recognized that women were acquiring HIV heterosexually (13, 14) and when almost 20,000 women had officially died of AIDS (15), women were absent from clinical trials (16), and the CDC AIDS case definition failed to include certain common disease manifestations unique to women.…”
Section: The Etiology Evolution and Advantages Of The Vulnerabilitymentioning
confidence: 99%
“…Close identification of the virus with gay men, and later injection drug users, meant that researchers failed to recognize or focus on heterosexual transmission for many years after the first cases were diagnosed in the US. Even by the 1990s, when it was recognized that women were acquiring HIV heterosexually (13, 14) and when almost 20,000 women had officially died of AIDS (15), women were absent from clinical trials (16), and the CDC AIDS case definition failed to include certain common disease manifestations unique to women.…”
Section: The Etiology Evolution and Advantages Of The Vulnerabilitymentioning
confidence: 99%
“…On the other hand, evidence indicates that women are still under-represented in neuropsychological studies of HIV. A review of 236 studies of neurological and neuropsychological complications of HIV indicated that from 1988 to 1997 only 31% of the studies included women with approximate representational parity, where representational parity meant that the representation of women was greater than or equal to 75% of the proportion of new cases of AIDS involving women (e.g., in 1988, to be classified as comparable, a study sample had to include at least 7.8% women, 7.8% being equal to 75% of new AIDS cases that were diagnosed among women in 1988 [10.4%]) (Fox-Tierney et al 1999). More recent data on representational parity in HIV research is lacking.…”
Section: Neurological Function In Hiv+ Women Versus Menmentioning
confidence: 99%
“…Newfound visibility meant that women might be less likely to be excluded from drug trials and from studies of disease progression than they had been in the past (Fox-Tierney et al 1999). At the juncture of a continually shifting base of medical knowledge, feminism, epidemiological classifications, sexual stratification systems, and the discursive realm, women were increasingly counted, and their attendant needs for care and prevention made more possible.…”
mentioning
confidence: 99%